Challenges of Implementing Integrated SIMRS at ABC Hospital, Bengkulu City - Ahmad Ridho Firmansyah (SMART : Jurnal Teknologi Informasi dan Komputer, 2025)
Hospital Management Information Systems (SIMRS) are a key component in improving the quality of health services and hospital operational efficiency. However, the implementation process is often faced with complex multidimensional challenges. This study aims to identify and analyze the challenges in the implementation of integrated SIMRS at RS ABC Kota Bengkulu using a mixed-method approach. The novelty of this research lies in the development of a Hospital IS Implementation Challenge Framework (HIICF) that integrates four dimensions of challenges — technological, human resources, organizational, and regulatory — into a comprehensive measurement instrument adapted to the context of Type C hospitals in Indonesia. Data were collected through in-depth interviews with 18 key informants, questionnaires distributed to 127 SIMRS users, and document analysis. Findings reveal that the most dominant challenge is the human resources dimension (mean 3.89/5.00), particularly staff digital competence and resistance to change, followed by technological infrastructure (3.74/5.00), organizational management (3.51/5.00), and regulatory compliance (3.12/5.00). The HIICF framework developed is validated with a Cronbach's Alpha value of 0.874, indicating high reliability. This research contributes to evidence-based guidance for SIMRS implementation in Type C hospitals across Indonesia.